Pengaruh Stres Kerja, Kecerdasan Emosional, Dan Komitmen Organisasi Terhadap Kinerja Karyawan Pada Quest San Hotel Denpasar - Dewi Siti Anjani; Made Yudi Darmita; Ni Luh Komang Julyanti Paramita Sari (Universitas Triatma Mulya, 2025)
In order to meet the objectives, the organization has to monitor employee performance. The present study was carried out at Four Points by Sheraton Bali, Seminyak, with the following objectives: 1) ascertain the impact of extrinsic motivation on employee performance; 2) confirm the impact of work discipline on employee performance; 3) confirm the impact of employee engagement on employee performance; 4) ascertain the extent to which extrinsic motivation, work discipline, and employee engagement influence employee performance; and 5) confirm the independent variables that predominately affect employee performance. With 74 employees as the sample size, a quantitative research methodology was employed. Saturated sampling, often known as a census, is used in this study. The descriptive analysis, T-test, multiple linear regression, classical assumption testing, research instrument quality testing, coefficient of determination, and standardized coefficients beta analysis are the data analysis procedures that are employed. The regression model, as indicated by the study's results, is Y = 4.601 + 0.137X1 + 0.259X2 + 0.339X3. The results show that: 1) maintaining a strong work ethic has a positive and significant influence on employee performance; 2) external incentives play a constructive and important role in improving employee performance; 3) active involvement and commitment of employees have a positive and significant impact on their performance; 4) when considering the combined impact of external incentives, work discipline, and employee engagement, they account for 39.7% of the variation in employee performance; and 5) employee engagement stands out as the most influential factor on employee performance, as indicated by the Standardized Beta Coefficient value of 0.352. The study's conclusion is that businesses should consider variables such as work discipline, employee engagement, and extrinsic incentives when creating policies and initiatives to boost worker performance.